TFE3-Expressing Perivascular Epithelioid Cell Tumor of the Breast - Hyunjin Kim; Jimin Kim; Se Kyung Lee; Eun Yoon Cho; Soo Youn Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Perivascular epithelioid cell tumor (PEComa) is a very rare mesenchymal tumor with a distinctive morphology and immunophenotype. PEComas usually harbor TSC2 alterations, although TFE3 translocations, which occur in MiT family translocation renal cell carcinoma and alveolar soft part sarcoma, are also possible. We recently experienced a case of PEComa with TFE3 expression arising in the breast. An 18-year-old female patient presented with a right breast mass. Histologically, the tumor consisted of epithelioid cells with alveolar structure and showed a diffuse strong expression of HMB45 and TFE3. TSC2 was preserved. Melan A and smooth muscle actin were negative. To our knowledge, this is the first Korean case of PEComa of the breast that intriguingly presented with TFE3 expression.